2000
DOI: 10.1017/s0021900200018180
|View full text |Cite
|
Sign up to set email alerts
|

Preservation results for life distributions based on comparisons with asymptotic remaining life under replacements

Abstract: We investigate some preservation properties of two nonparametric classes of survival distributions and their duals, under appropriate reliability operations. The aging properties defining these nonparametric classes are based on comparing the mean life of a new unit to the mean residual life function of the asymptotic remaining survival time of the unit under repeated perfect repairs. They are motivated from a point of view that realistic notions of degradation, applicable to repairable systems, should be base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Example 19. Consider the following data in Bhattacharjee et al [9]; these data represent set of 40 patients suffering from It was found that̂= 0.0892 which is greater than the critical value of Table 1. Then we reject the null hypothesis of exponentiality and accept K which states that the data set has NBRU rp property.…”
Section: Numerical Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Example 19. Consider the following data in Bhattacharjee et al [9]; these data represent set of 40 patients suffering from It was found that̂= 0.0892 which is greater than the critical value of Table 1. Then we reject the null hypothesis of exponentiality and accept K which states that the data set has NBRU rp property.…”
Section: Numerical Resultsmentioning
confidence: 96%
“…The past decades witnessed some aging notions based on a stochastic comparison between a random life and its equilibrium version * which are introduced and studied (cf. Li and Xu [14], Bhattacharjee et al [9], and Ahmad et al [27]). This section investigates the following new aging notion.…”
Section: Related Aging Classesmentioning
confidence: 97%
See 1 more Smart Citation
“…See Bhattacharje, Abouammoh, Ahmed, and Barry [5] and Ahmad and Mugdadi [1] for example. See Bhattacharje, Abouammoh, Ahmed, and Barry [5] and Ahmad and Mugdadi [1] for example.…”
Section: Definition 28: a Lifetime Random Variable X With Finite Meamentioning
confidence: 99%